Arrogant pride and its relationship to the narcissistic personality of the sons of Al Thuraya - Abdel Hussein Alwan, Nasra (Journal of College of Education, 2022)
Research summary The current research aims to identify the arrogant bragging among the sons of the Pleiades, and the significance of the statistical differences in the arrogant bragging according to the gender variable (males - females), and to identify the narcissistic personality of the sons of the Pleiades, and the significance of the statistical differences in the narcissistic personality according to the gender variable (males - females). And the detection of the correlation between the arrogant pride and the narcissistic personality of the sons of Al Thuraya, and the research sample of (400) for both sexes was selected with different educational attainment and ages, with (200) males and (200) females chosen by random stratified method, from students of education Diyala for the academic year (2020-2021) in Diyala Governorate, and after reviewing the literature and previous studies, the researcher did not find an appropriate tool for the research sample. 27) Paragraph, and the psychometric properties of the two scales were extracted, as the researcher extracted the apparent validity of the two scales after presenting them to a group of arbitrators in educational and psychological sciences. Statistically using the Statistical Package for Social Sciences (SPSS) and the results showed the following: • There is arrogance and narcissistic personality among the sons of Thuraya. • There are no statistically significant differences in arrogance and narcissistic personality according to the gender variable (male - female). • The existence of a direct significant correlation between the research variables, the arrogant pride and the narcissistic personality. In light of the results, the researcher reached a set of conclusions, recommendations and suggestions.